2015
DOI: 10.1007/s00432-015-1992-4
|View full text |Cite
|
Sign up to set email alerts
|

Androgens enhance the glycolytic metabolism and lactate export in prostate cancer cells by modulating the expression of GLUT1, GLUT3, PFK, LDH and MCT4 genes

Abstract: The results obtained establish androgens as modulators of glycolytic metabolism in PCa cells by stimulating glucose consumption, as well as the production and export of lactate, which may represent a crucial issue-driven prostate tumor development. These findings also highlight the importance of PCa therapies targeting AR and metabolism-related proteins.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
38
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(43 citation statements)
references
References 47 publications
4
38
0
1
Order By: Relevance
“…Therefore, our findings suggest that these processes may play a critical role in mediating the deleterious effects of androgens in the physiology of the renal cells. In this sense, DHT has been shown to alter glycolytic metabolism and impair mitochondrial function in other cell types (66,67). As recently reported by Wang et al, pancreatic islets from DHT-treated rats showed significant changes in the levels of several key genes involved in mitochondrial biogenesis, mitochondrial oxygen consumption rate, and ATP production.…”
Section: Figsupporting
confidence: 55%
See 1 more Smart Citation
“…Therefore, our findings suggest that these processes may play a critical role in mediating the deleterious effects of androgens in the physiology of the renal cells. In this sense, DHT has been shown to alter glycolytic metabolism and impair mitochondrial function in other cell types (66,67). As recently reported by Wang et al, pancreatic islets from DHT-treated rats showed significant changes in the levels of several key genes involved in mitochondrial biogenesis, mitochondrial oxygen consumption rate, and ATP production.…”
Section: Figsupporting
confidence: 55%
“…The authors also demonstrated that androgens can directly impair beta cell function by inducing mitochondrial dysfunction in vitro in an AR-dependent manner (66). In a different context, DHT enhanced glucose consumption and lactate export in prostate cancer cells (67).…”
Section: Figmentioning
confidence: 96%
“…Like MYC, AR regulates expression of many genes involved in glutamine and glucose metabolism. Androgen signaling stimulates glucose consumption as well as production and export of lactate by upregulating the expression of GLUT1/GLUT3, phosphofructokinase 1 (PFK 1), monocarboxylate transporter 4 (MCT4), and calmodulin-dependent kinase kinase 2 (CAMKK2) genes [76,77]. CAMKK2 is highly upregulated in PCa, and CAMKK2-dependent activation of AMP-regulated kinase (AMPK) results in an increased PFK1 activity and promotes glucose uptake and lactate production [78].…”
Section: Androgen Signaling and Pca Metabolismmentioning
confidence: 99%
“…70 However, these transporters, particularly GLUT1, are downregulated by DHT in non-tumor Sertoli cells. 71 Thus, hormonal regulation of GLUT1/3 seems to be tissuedependent.…”
Section: Glut Transporters As Clinical Targets In Pcamentioning
confidence: 99%